THE HUMAN NUTRITION SYSTEM OF THE MEDIEVAL POPULATION OF THE PERM CIS-URALS, AS AN INDICATOR OF BIOLOGICAL AND SOCIAL ADAPTATION (according to anthropological data) - Bryukhova, N.G. (Perm Federal Research Centre Journal, 2016)
The paper suggests a reconstruction of the human nutrition system of the medieval inhabitants of Perm Krai. The study is based on an analysis of the anthropological materials using the first results of isotopic analyses made for the problem under consideration.